1999
DOI: 10.4269/ajtmh.1999.61.187
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of dihydroartemisinin against clinical isolates of Plasmodium falciparum in Yaounde, Cameroon.

Abstract: Abstract. The in vitro activities of dihydroartemisinin (the biologically active metabolite of artemisinin derivatives), chloroquine, monodesethylamodiaquine (the biologically active metabolite of amodiaquine), quinine, mefloquine, halofantrine, and pyrimethamine were assessed in 65 African isolates of Plasmodium falciparum from Yaoundé, Cameroon using an isotopic microtest. The 50% inhibitory concentration (IC 50 ) values for dihydroartemisinin were within a narrow range from 0.25 to 4.56 nM, with a geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
6
22
3
Order By: Relevance
“…26 Our previous in vitro studies on African isolates have suggested that cross-resistance may occur between chloroquine and quinine and between amino alcohols and artemisinin derivatives. [27][28][29][30] A similar trend of cross-resistance patterns was observed in the present study. In vitro cross-resistance between these drugs has also been confirmed in other independent studies in Senegal and Thailand.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…26 Our previous in vitro studies on African isolates have suggested that cross-resistance may occur between chloroquine and quinine and between amino alcohols and artemisinin derivatives. [27][28][29][30] A similar trend of cross-resistance patterns was observed in the present study. In vitro cross-resistance between these drugs has also been confirmed in other independent studies in Senegal and Thailand.…”
Section: Discussionsupporting
confidence: 75%
“…34 However, the extent to which multiple parasite populations in a given isolate influence in vitro response to amino alcohols and artemisinin derivatives is probably limited in Yaoundé, where regular in vitro monitoring of drug response has shown their high activity. 23,29,30 In conclusion, it does not seem to be clear at present whether there is a distinct set of pfmdr1 mutations that are strongly associated with resistance to amino alcohols and artemisinin derivatives in field isolates in Africa. The main reason may be related to the high clinical efficacy of these drugs in Africa, in contrast to Southeast Asia where clinical failure is frequently observed when monotherapy with quinine, mefloquine, or halofantrine is administered.…”
Section: Discussionmentioning
confidence: 99%
“…25,[29][30][31] We have also demonstrated that a similar proportion of Cameroonian patients, including adults and children Ն 5 years old, failed to clear asexual parasitemia and symptoms associated with malaria infection within 14 days after the standard chloroquine therapy. 18,19,27 Thus, our in vitro and in vivo data are concordant and support the observation that a relatively high proportion of P. falciparum isolates in Yaounde are chloroquine-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Classical isotopic (48-h) method was used for in vitro DHA monitoring (Desjardins et al, 1979). DHA was the most potent drug (geometric mean IC50 = 1.11 nM, 95% confidence interval = 0.96-1.28 nM, range = 0.25-4.56 nM, n = 65) among the panel of drug compounds tested (Ringwald et al, 1999).…”
Section: Studies Assessing In Vitro and Ex-vivo Efficacy Methods Of Amentioning
confidence: 99%